(untitled) (Journal of Informatics and Mathematical Sciences, 2024)
Transportation problems are widely used in supply chain management and logistics to reduce costs.When the costs of unit transportation, demand, and supply are all provided precisely, then efficient algorithms have been presented to solve the transportation problem. In this research, we transform the fuzzy transportation problem into a crisp valued transportation problem by using a ranking method. Here, we first simplify the fuzzy transportation problem using the robust ranking approach to obtain an initial basic feasible solution. Next, we apply the MODI method to obtain the fuzzy optimal solution. Ranking method is an appropriate method in ranking fuzzy numbers which is demonstrated with numerical example.